2021
DOI: 10.3390/genes13010070
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of the Mouse Ath28 Locus Yields Three Atherosclerosis Modifying Sub-Regions

Abstract: A mouse strain intercross between Apoe−/− AKR/J and DBA/2J mice identified three replicated atherosclerosis quantitative trait loci (QTLs). Our objective was to fine map mouse atherosclerosis modifier genes within a genomic region known to affect lesion development in apoE-deficient (Apoe−/−) mice. We dissected the Ath28 QTL on the distal end of chromosome 2 by breeding a panel of congenic strains and measuring aortic root lesion area in 16-week-old male and female mice fed regular laboratory diets. The parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Some evidence suggests female sex hormones sensitize inflammation in atherogenesis ( 7) but as males get older, they are more prone to plaque formation (25). Mapping mouse atherosclerosis modifier genes in some congenic mouse strains yielded replicating results in females and males but the extent of atherosclerosis plaques appears to be slightly higher in females where the data were normally distributed but was skewed in males (39), somewhat comparable to our results. In our study, we found significant differences in atherosclerotic lesions between groups, with gonadally intact WT females having two to three times bigger atherosclerotic lesions than all other groups: gonadally intact males, prepubertally gonadectomized males and females, and agonadal SF-1 KO mice.…”
Section: Discussionsupporting
confidence: 85%
“…Some evidence suggests female sex hormones sensitize inflammation in atherogenesis ( 7) but as males get older, they are more prone to plaque formation (25). Mapping mouse atherosclerosis modifier genes in some congenic mouse strains yielded replicating results in females and males but the extent of atherosclerosis plaques appears to be slightly higher in females where the data were normally distributed but was skewed in males (39), somewhat comparable to our results. In our study, we found significant differences in atherosclerotic lesions between groups, with gonadally intact WT females having two to three times bigger atherosclerotic lesions than all other groups: gonadally intact males, prepubertally gonadectomized males and females, and agonadal SF-1 KO mice.…”
Section: Discussionsupporting
confidence: 85%